Low Serum Insulinlike Growth Factor II Levels Correlate with High BMI in American Indian Adults. Issue 3 (6th February 2020) - Muller, Yunhua L.; Hanson, Robert L.; Mahkee, Darin; Piaggi, Paolo; Kobes, Sayuko; Hsueh, Wen‐Chi; Knowler, William C.; Bogardus, Clifton; Baier, Leslie J.
Abstract : Objective: Insulinlike growth factor II (IGF‐II) regulates metabolism and growth. In humans, both positive and negative relationships have been reported between serum IGF‐II levels and obesity. This study assessed the relationship between serum IGF‐II levels and BMI and determined whether IGF‐II levels predict weight gain. Methods: Serum samples were available from 911 American Indians with a recorded BMI. IGF‐II was measured using enzyme‐linked immunosorbent assay. Results: Serum IGF‐II levels were negatively correlated with BMI ( r = −0.17, P = 4.4 × 10 −7, adjusted for age, sex, and storage time). The strongest correlation was in participants aged ≥ 30 years ( r = −0.28, P = 3.4 × 10 −8, N = 349), a modest correlation was in participants aged 20 to 29 years ( r = −0.15, P = 7.6 × 10 −3, N = 322), and participants aged 15 to 19 years had no correlation ( r = 0.05, P = 0.48, N = 240). IGF‐II levels did not predict weight gain. However, among individuals who had genotypes for 64 established obesity variants (age ≥ 20 years, N = 671), a genetic risk score for high BMI was associated with lower IGF‐II (β = −0.08 SD of IGF‐II per SD of the genetic risk score, P = 0.025). Conclusions: There is a negative relationship between IGF‐II levels and BMI, in which the correlation is stronger at older ages. The association between genetic risk for BMI and IGF‐II levels suggests that this correlation may be due to an effect of obesity on IGF‐II.